Understanding in mathematics - Sierpinska, Anna (Falmer, 1994)
The concept of understanding in mathematics with regard to mathematics education is considered in this volume, the main problem for mathematics teachers being how to facilitate their students' understanding of the mathematics being taught.
Keywords: Mathematics -- Study and teaching -- Psychological aspects.; Comprehension.; Education -- Curricula.; Mathematics -- Study and teaching -- Psychology.; Curriculum; Mathématiques -- Étude et enseignement -- Psychologie.; Compréhension.; Programmes d'études.; Mathématiques -- Étude et enseignement -- Aspect psychologique.; curricula.; EDUCATION -- Educational Psychology.; Mathematics -- Study and teaching -- Psychology; Education -- Curricula; Comprehension; Mathematics -- Study and teaching -- Psychological aspects; Schools -- Curriculum -- Mathematics